THE IMPORTANCE OF CULTIVATION OF CROSS-CULTURAL COMMUNICATION SKILLS OF STUDENTS IN THE CONTEXT OF MULTICULTURALISM - Ran, Cao; Sarsenbayeva, Lyaziza (Pedagogy and Psychology, 2021)
With the popularization of the internationalization concept of higher education, the field of international exchanges and cooperation between universities continues to expand, and the university campus has increasingly become an important place for the intersection of multiculturalism. In this multi-cultural context, the cross-cultural communication skills of teachers and students in colleges and universities are put forward new challenges. Having strong cross-cultural communication skills is not only an important embodiment of the improvement of the comprehensive quality of students, but also one of the important skills necessary for students in their study and work. The article reveals the factors of development of students’ skills in mechanic-cultural communication.